A Conceptual Paradigm of Al-Nafs in the Tafsirs of Al-Ṭabarī and Al-Rāzī: Tracing Epistemological Shifts in the Classical Exegetical Tradition - Nida Husna Abdul Malik; Rosihon Anwar; Solehudin Solehudin; Izzah Faizah Siti Rusydati Khairani (UIN Sunan Gunung Djati Bandung, 2026)
This article examines the concept of al-nafs in classical exegesis through a comparative approach to two great exegetes, namely al-Ṭabarī and Fakhr al-Dīn al-Rāzī. By focusing on three key verses, namely QS Yūsuf [12]:53, al-Qiyāmah [75]:2, and al-Fajr [89]:27–30, this study changes the epistemological shift in the construction of the meaning of the human soul from the traditional bayānī approach to a philosophical and psychological approach. Through the methods of text analysis and philosophical hermeneutics, it is found that al-Ṭabarī's exegesis emphasizes the authority of riwāyah and normative meaning, while al-Rāzī integrates rational, spiritual, and Sufi elements in his interpretation. These findings not only demonstrate the rich intellectual heritage of classical exegesis but also open up opportunities for actualizing the concept of al-nafs in the context of Islamic psychology, character education, and modern spirituality. Within a contemporary hermeneutical framework, this article proposes a rereading of exegesis as a space for historical and existential dialogue relevant to the challenges faced by today's Muslim community.